Sex and authorship in global cancer research - Deborah Mukherji; Ophira Ginsburg; Grant Lewison; Richard Sullivan; Verna Vanderpuye; Winnie K W So; Miriam Mutebi; Nazik Hammad; Julie Torode; Erica Liebermann (BMJ Oncology, 2024)
Introduction Research is an essential pillar of cancer control and key in shaping regional cancer control agendas. Imbalances in science and technology in terms of lack of female participation have been well documented. However, there is little evidence about country-level female participation in cancer research.Methodology Through a complex filter, cancer research papers were identified and grouped by countries and sex of the first and last authors of each paper and analysed by the percentage of females in these positions alongside other parameters.Results Our analysis of 56 countries’ outputs, in 2009, revealed that females were the first authors in 37.2% and last authors in 23.3% of papers. In 2019, females were the first author in 41.6% and last author in 29.4% of papers. Females increased as first authors by 26%, and as last authors by 12% between these two time periods. The top performing countries in terms female/male parity for first or last authorship were in Eastern and Southern Europe as well as Latin American countries.From 2009 to 2019, the highest proportion of females as first and last authors were from low-income and middle-income countries in Latin America and Eastern Europe.Females were more likely to publish in lower impact journals and were less likely to be cited compared to males.Conclusions Globally, progress in female’s authorship in oncology research has been uneven. More research is needed to understand the reasons behind this. Advancing diversity and equity in research leadership and authorship will be essential to address the complex challenges of cancer globally.